2018
DOI: 10.1177/1177271917751900
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Procalcitonin in Pediatric Patients on Extracorporeal Membrane Oxygenation

Abstract: Objectives:To assess the kinetics of procalcitonin (PCT) and C-reactive protein (CRP) in pediatric patients who required extracorporeal membrane oxygenation (ECMO) and to analyze its relationship with morbidity and mortality.Patients and methods:Prospective observational study including pediatric patients who required ECMO. Both PCT and CRP were sequentially drawn before ECMO (P0) and until 72 hours after ECMO.Results:A total of 40 patients were recruited. Two cohorts were established based on the value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
2
4
0
Order By: Relevance
“…Left shift and CRP markers also showed no changes, both with no typical curve in relation to infection and no higher elevation in patients with confirmed infection, in agreement with Rungatscher’s et al 18 and Bobillo’s et al 26 studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Left shift and CRP markers also showed no changes, both with no typical curve in relation to infection and no higher elevation in patients with confirmed infection, in agreement with Rungatscher’s et al 18 and Bobillo’s et al 26 studies.…”
Section: Discussionsupporting
confidence: 88%
“…Absolute neutrophil count did not vary according to the presence or absence of infection, concordant with that described by Coffin, Steiner, and Kaczala. 5,7 Left shift and CRP markers also showed no changes, both with no typical curve in relation to infection and no higher elevation in patients with confirmed infection, in agreement with Rungatscher's et al 18 and Bobillo's et al 26 studies.…”
Section: Inflammatory Markerssupporting
confidence: 86%
“…77 However, an article on adults 64 concluded that PCT was not modified by entry into ECMO and that it might be a good biomarker of severe infection in these patients. In a recent article that analyzed 40 pediatric patients in ECMO, 78 PCT seemed to produce the expected kinetics for the pathology that conditioned ECMO support, but data about the relation of PCT and infection in ECMO are still weak (Table 4). Therefore, more studies are required to evaluate the usefulness of PCT as a biomarker of infection and morbidity in these patients.…”
Section: Procalcitonin and Bacterial Infection Diagnosismentioning
confidence: 99%
“…Although clinicians with access to PCT use serial measurements to determine clinical improvement and response to antibiotics, data describing the kinetics of PCT in children are lacking [20][21][22][23]. To determine whether PCT can be used as a surrogate of clinical response to help guide antibiotic de-escalation in non-critically ill children, we evaluated the kinetics of PCT among children with non-critical acute bacterial infections who are receiving effective antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%